Transform your class! Bridging the concepts of indigenous knowledge and biotechnology education - Intan Nurnilam Sari; Siti Zubaidah; Susriyati Mahanal; Hadi Suwono (University of Muhammadiyah Malang, 2025)
Biotechnology education in many contexts remains dominated by Western-oriented scientific paradigms, leading students to engage with abstract laboratory-based concepts while overlooking the rich local knowledge that forms the cultural and scientific foundations of their communities. This study explores the transformative learning experiences of high school students through the integration of Indigenous Knowledge into biotechnology education in Indonesia. The urgency of this research lies in the need to decolonize science education and make it more relevant to cultural contexts often marginalized in formal curricula. Using an ethnographic case study approach, data were collected through classroom observations, student reflections, interviews with students and community elders, and analysis of student projects focusing on the utilization of traditional nira sap in Lamongan. The participants were 36 tenth-grade students from SMAN 1 Paciran, East Java. Findings show that transformative learning occurred through students’ dynamic interactions with cultural “other(s)” in history, in memory, and with intimacy. These interactions led students to challenge their taken for granted assumptions about science, culture, and identity. This article contributes to the discourse on transformative education by illuminating how local cultural knowledge can serve as a catalyst for personal and epistemological transformation in science education.